You Must Touch It: Touchscreen Hygiene and the Sin of the Smudge. (April 2023) - Plotnick, Rachel
This article examines how people have constructed touchscreen smudges, those oily marks left behind by users' fingers on shiny glass, as a form of 'mess'. It offers an historical account of smudges between 2007 and 2010, when users, corporations, journalists, third-party accessory manufacturers and others began to first frame smudges as a problem for mobile media due to users' constant touching and the evidence of their finger trails which functioned as a kind of ' visible tactility '. Solutions took the form of engineering special screen coatings or cultivating responsible users who would maintain their devices through cleaning and caretaking practices. In both these cases, smudges were denigrated not for degrading media content or breaking the device's functionality, but rather for violating high-tech aesthetics and drawing attention to porous, tactile and germ-riddled bodies. The piece, bringing together this case with the present, encourages scholars to attend to the ways that users are entreated to tame and groom both their bodies and their media devices in particular socio-historical contexts.